No-code workflow automation for meeting minutes generation using scrum - Syafika Zalfanissa Dila; Vitri Tundjungsari (Institute of Computer Science (IOCS), 2026)
The increasing frequency of online meetings has intensified the need for efficient and consistent meeting documentation. However, the preparation of meeting minutes is still commonly performed manually, resulting in delayed documentation, inconsistent formats, and increased workload. This study aimed to develop and evaluate a no-code workflow automation system for meeting minutes generation using the Scrum framework. The proposed system integrated a no-code automation platform with an AI-based text summarization service to automatically process meeting transcripts and generate structured meeting minutes consisting of key discussion points, decisions made, and action items. The system was developed using an iterative Scrum-based approach, allowing continuous feedback and refinement throughout the development process. System evaluation focused on efficiency and usability by comparing the automated process with manual documentation. The results showed that the proposed system reduced the meeting minutes preparation time from approximately 30–45 minutes per meeting (manual process) to 2–5 minutes per meeting (automated workflow), while improving consistency and clarity of the output. In addition, the no-code approach enabled non-technical users to operate and maintain the system without requiring programming skills This study demonstrated that combining no-code workflow automation, AI-based text summarization, and agile development practices can provide an effective and practical solution for automating meeting documentation in organizational environments.